Interactive Stories And Video Game Art : A Storytelling Framework for Game Design - Solarski, Chris, ....- (New York : CRC Press, 2017)
The success of storytelling in games depends on the entire development team—game designers, artists, writers, programmers and musicians, etc.—working harmoniously together towards a singular artistic vision. Interactive Stories and Video Game Art is first to define a common design language for understanding and orchestrating interactive masterpieces using techniques inherited from the rich history of art and craftsmanship that games build upon. Case studies of hit games like The Last of Us, Journey, and Minecraft illustrate the vital components needed to create emotionally-complex stories that are mindful of gaming’s principal relationship between player actions and video game aesthetics. This book is for developers of video games and virtual reality, filmmakers, gamification and transmedia experts, and everybody else interested in experiencing resonant and meaningful interactive stories.
Keywords: Design; Programmeren; Storytelling; Video Games